Transformational and transactional leadership and knowledge sharing in Nigerian university libraries. (October 2020) - Ugwu, C. I.; Onyancha, O. B.; Fombard, M.
This study aims to investigate the influence of transformational and transactional leadership styles on the knowledge-sharing practices of librarians. It adopted a quantitative approach and a questionnaire formed the main instrument of data collection. Data collected from 216 librarians in different private, state and federal university libraries in Nigeria was analysed using multiple regression techniques and Tukey's post-hoc test of honestly significant difference. The findings revealed that transformational leadership impacted knowledge sharing more than transactional leadership styles. Therefore, this study provides empirical evidence that transformational and transactional leadership behaviours are required to enhance the knowledge-sharing activities of librarians in Nigeria.